Sosialisasi Aplikasi Penghitung Zakat bagi Masyarakat - Taufiq Iqbal; Candra Zonyfar; Fuadi; Ijal Fahmi; Syamsul Rizal; Ismail (Yayasan Kawanad, 2023)
Zakat is important for encouraging social awareness and correcting economic inequality, but there are still many people who do not understand how to calculate it due to several factors such as lack of understanding, outreach, and difficulty in manual calculations. In February 2023, a socialization of the zakat counter application was held for the people of Bireun Regency. This activity aims to increase understanding of zakat and facilitate the process of calculating zakat. In this event, the public was given an explanation on how to use the zakat counter application and it was hoped that they would be able to calculate zakat more easily and accurately. The expected results are increasing awareness about the importance of zakat and benefiting from the zakat counter application in helping the process of calculating zakat more effectively and efficiently. With the zakat counter application, it is hoped that it can increase the amount of zakat collected to help people in need. In addition, this socialization is also expected to strengthen cooperation between the government and the community in developing a better zakat calculating application in the future. Therefore, organizing the socialization of the zakat calculating application in Bireun Regency is an important step to increase public awareness about zakat and facilitate the process of calculating zakat effectively and efficiently.